(3eTcdGJ GdUMjMjfs - (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL, GHf GdLhRj , J (B597 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO ajg CKfGA cTa GdeTcd ef eSfO CHj HcQ GdUOjb QVi Gddg Yfg bhdg (B: (3hcfG fQi Cf dfG ai gPG GdCeQ MbkG GdMOjK GdChd ef CaQGO GdHNGQi s
(3BNQgG (B:s
(3BNQ GdehLhO efg CKfGA cTa GdeTcd ef MOjK YHO Gddg Hf YeQ Hf GdNWGH QVi Gddg YfgeG bhdg hai GdMOjK GdKGfi hGdYTQjf HYO GdeGFI (B: (3eKd UGMH GdbQBf ceKd UGMH GdEHd GdeYbdI s
(3GdChQGb GdCNjQI cJHJ HNW eZGjQs
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B316 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B157 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B520s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
Keywords: (3GdMOjK h GdeUWdMs